Resistance to trypanosomosis: Of markers, genes and mechanisms - Teale, A.J.; Agaba, Morris; Clapcott, S.J.; Gelhaus, A.; Haley, C.; Psifidis, A.; Horstmann, R.; Iraqui, F.; Kemp, Stephen J.; Nilsson, P.; Schwerin, M.; Sekikawa, K.; et al. (1999)
A two species comparative genome scanning approach has been taken to mapping, and eventually identifying, genes at quantitative trait loci (QTL) influencing resistance to trypanosomosis due to infection with Trypanosoma congolense. Using two large murine F2 and two F6 advanced intercross populations, QTL influencing survival time in mice following challenge with T. congolense were mapped to small confidence intervals on MMU1, 5 and 17. The QTL on MMU17, Tirl, has a sufficiently small confidence interval (<1cM) to justify an immediate search for positional candidate genes at the DNA level. Mapping of trypanotolerance loci in an F2 cattle resource population is now beginning to reveal bovine resistance QTLs. A key strength of the comparative strategy derives from overlaying the genetic maps of murine and bovine QTL - containing regions. If, and where, the same genes are used by the two species, this may facilitate localisation of one or more of the genes contributing to variation in resistance to T. congolense trypanosomosis.